Differential Tropism of SARS-CoV and SARS-CoV-2 in Bat Cells - Lau, Susanna K.P. (Emerg Infect Dis, 2020)
Severe acute respiratory syndrome coronavirus 2 did not replicate efficiently in 13 bat cell lines, whereas severe acute respiratory syndrome coronavirus replicated efficiently in kidney cells of its ancestral host, the Rhinolophus sinicus bat, suggesting different evolutionary origins. Structural modeling showed that RBD/RsACE2 binding may contribute to the differential cellular tropism.